Mechanical Properties Characterizations of Cassava Starch using Glycerol and Sorbitol Plasticizer - Lailatin Nuriyah; Siti Jazimah Iswarin; Wiyono Wiyono (Natural B, Journal of Health and Environmental Sciences, 2011)
Bioplastic is a kind of plastic that biodegradable, and is made from renewable materials. This experiment has been intended to produce bioplastic from biopolymer such as: cassava flour, gelatin, jelly, with glycerol and sorbitol plasticizers.  The basic materials (flour, gelatin, and jelly) compared to plasticizer is 3:2. The first sample is made with various amounts of gelatin and cassava flour, with a certain amount of plasticizer; the second sample is made with basic material are fixed, and plasticizer are varied. Syntheses were done by blending method at 90 °C. The mixing is done until the solution is homogeny, and then casting into the caster. The characterization mechanical test includes strain and stress with prior heating at 5°C, 25 °C and 45 °C. Strain test maximum is 2,456 N/mm2 for sample K3-L with prior heating at 45°C, and maximum stress of 115 % for sample K5-L at 25 °C.  The Influence of variation of flour, gelatin, sorbitol and glycerol to tension is not predictable.